Pengendalian Kualitas Ban Vulkanisir Di CV. Sinar Kencana Dengan Metode SQC - Nia Kurniasih; Khasbunalloh; Patria Adhistian (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
CV. Sinar Kencana Abadi is a service company engaged in the field of retreading used tires that are processed into new tires. In its production process, the company still has a challenge in the form of defects in tire products caused by internal and external factors of the company, so that the products produced do not meet the quality standards set by the company. The purpose of this study is to identify the cause of defects in retreaded tires, to analyze whether product defects are still within control limits and to provide suggestions for improvement to improve the quality of retreaded tire products at CV. Sinar Kencana Abadi. This study uses a statistical quality control (SQC) method and applies seven tools with the following research results, the factors that cause defects are Inflated Tires and Unripe Tires in retreaded tire products. From the two defects, it is known that the total defect in Inflated Tires is 75pcs and the total defect in Unripe Tires is 71pcs. This is due to five factors such as humans, machines, methods, raw materials, and the environment which are the root of the problem. And then the company makes improvements to optimize its production process, including providing training to employees, carrying out routine machine maintenance, and selecting good raw materials as well as conducting direct supervision of defective products produced.